IT’S OKAY NOT TO BE OKAY: PASTORAL KONSELING SEBAGAI PILAR PENGUATAN BAGI PASIEN PENYAKIT TERMINAL - Salindeho, Veibe; Sumakul, Yunita; Katiandagho, Pramesti (PT. Giat Konseling Nusantara, 2025)
This article discusses the role of pastoral counseling as a pillar of strengthening for terminal illness patients. Through a qualitative approach with a case study method, this study explores the experiences of patients, families, and pastoral practitioners in dealing with emotional and spiritual challenges. Findings show that pastoral counseling provides emotional validation, spiritual support, and improves family relationships, which contribute to the well-being of patients. This assistance not only helps patients accept the reality of death, but also provides meaning in their suffering. Thus, this study emphasizes the importance of integrating pastoral counseling in the healthcare system, especially in palliative care, to create a supportive environment for patients and their families.